2005
DOI: 10.1111/j.1439-0434.2004.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of RT–PCR for the Detection of Bean leaf roll virus in Plant Hosts and Insect Vectors

Abstract: The detection of luteoviruses by reverse transcription polymerase chain reaction (RT-PCR) depends on the adequate quality and quantity of extracted viral nucleic acids. We have optimized the detection of Bean leaf roll virus (BLRV) using selective precipitation by LiCl of viral RNA from a small quantity of infected plant tissues and insect vectors. The optimal template for PCR was 15 ll of RT reaction mixture. BLRV was detected in different plant hosts and aphid vectors and Aphis fabae, previously considered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…One μL of total RNA template was used for each RT-PCR reaction. Bean leaf roll virus was amplified with the specific primers BLRV F Ortiz and BLRV R Ortiz and thermocycling conditions as described by Oritz et al (2005), yielding a 385 bp product. Beet western yellows virus was amplified with specific primers BWYF and BWYV PCR and thermocycling conditions as described by Miranda et al (1995), yielding a 428 bp product.…”
Section: Pcrmentioning
confidence: 99%
“…One μL of total RNA template was used for each RT-PCR reaction. Bean leaf roll virus was amplified with the specific primers BLRV F Ortiz and BLRV R Ortiz and thermocycling conditions as described by Oritz et al (2005), yielding a 385 bp product. Beet western yellows virus was amplified with specific primers BWYF and BWYV PCR and thermocycling conditions as described by Miranda et al (1995), yielding a 428 bp product.…”
Section: Pcrmentioning
confidence: 99%
“…Many studies for field survey of CABYV incidence showed enzyme linked immunosorbent assay (ELISA) using antibody specific to CABYV was effective for the CABYV detection method ( Abou-Jawdah et al, 2000 ; Deng et al, 1997 ; Kassem et al, 2007 ; Mnari-Hattab et al, 2005 ). In recent reports, ELISA is not sensitive enough to detect the presence of CABYV and other luteoviruses in plants ( Figueira et al, 1997 ; Oritz et al, 2005 ; Van den Heuvel et al, 1989 ). We set up the molecular detection method, RT-PCR, for diagnosis of CABYV in this study and showed the RT-PCR analysis is highly reliable to detect CABYV in suspicious samples.…”
Section: Discussionmentioning
confidence: 99%
“…Le MWMV n'a pas été détecté au niveau des 175 échantillons de cucurbitacées collectés bien que ce virus est transmis par le puceron Aphis gossypii très présent en Tunisie (Mnari-Hattab & Cherif, 1992; Ben Halima-Kamel & Ben Hamouda, 1993) et dont l'efficacité de transmission de ce virus est de 31 à 56%, (Quiot-Douine et al ., 1990). Ainsi, l'absence de ce virus dans les échantillons testés pourrait être due soit à son absence réelle en Tunisie, soit à la faible sensibilité des tests sérologiques qui sont 10 4 moins sensibles que les tests moléculaires ou qui ne détectent pas certains serotypes éloignés (van den Heuvel & Peters, 1989;Figueira et al ., 1997;Ortiz et al ., 2005). Le MWMV a été détecté au Maroc sur melon et courgette (Fischer & Lockhart, 1974), et au Soudan en 1994 sur C. melo var.…”
Section: Discussionunclassified